Effects of Different Maturity Stages on Antioxidant Content of Ivorian Gnagnan (Solanum indicum L.) Berries - Furio Brighenti; Nicoletta Pellegrini; Massimiliano Rinaldi; Francesca Scazzina; Teresa Mazzeo; Luca Calani; Daniele Del Rio; Denis N’Dri (Molecules, 2010)
Gnagnan (Solanum indicum L.) is a spontaneous plant widely distributed in Ivory Coast. During ripening stages, Solanum indicum L. presents different colours (green, yellow and red) and is reported to contain several albeit poorly characterized antioxidant compounds. This paper describes in detail the antioxidant profile (ascorbic acid, carotenoids and polyphenols), antioxidant capacity (FRAP test and Folin-Ciocalteau assay) and the colour changes of Gnagnan berries at different ripening levels. Ascorbic acid content was similar in green and yellow berries, but significantly lower in red ones. Red berries showed a higher content of carotenoids compared to green and yellow ones. Regarding polyphenols, several phenolic acids and flavonoids were found in all berries. The content of caffeoylquinic acids, caffeic acid, flavonol glycosides and naringenin was higher in red berries, while the content of p-coumaric acid and feruloylquinic acids was similar among the three colours. The FRAP assay increased with the ripening process, whereas total polyphenols were similar among berries. Significant differences were found for the colorimetric indexes among products of different degrees of ripening. The present results show the important role of the ripening stage in increasing the antioxidant content of Gnagnan berries.